Upaya Peningkatan Motivasi Belajar Bahasa Inggris Pada Mahasiswa Ibrahimy Genteng Banyuwangi - Mufidah Yusroh (IAI Darussalam, 2016)
Motivation is one of the causes of learning process especially in learning English. Motivation is divided into intrinsic and extrinsic motivation. Dealing with this, it can be drawn that motivation is the most important thing in learning English especially for those who have low ability in English. Thus, the purpose of this study is to determine: (1) the causes of the college students of IAI Ibrahimy Genteng who have low motivation in learning English and (2) how to increase the low motivation of the college students of IAI Ibrahimy Genteng in learning English. Then, this study will use a qualitative approach with case study. At the end of this research, it is expected to have many contributions in teaching and learning English especially for those who have difficulties in gaining English